Окреме провадження і народні засідателі: історико-правовий огляд - Ясинок, М.М. (Часопис Київського університету права, 2009)
В статье проведено исследование истории образования и развития института народных заседателей в гражданском процессе Украины. Проанализированы проблемы, возникшие в связи с введением этого института в систему современного гражданского процесса. In article research which concerns history of formation and development of institute of jurymen in civil legal proceedings of Ukraine is executed, problems which have arisen at input of the given institute in compound modern civil process - separate manufacture are analyzed.